The Effectiveness of the Module Static Fluid with Authentic Learning to Train Students' Problem-Solving Skills - Zakiah Arsyad; Mustika Wati; Suyidno Suyidno (SEJ (Science Education Journal), 2020)
Authentic learning includes the necessary foundation in learning physics. However, the limitations of the physics module based on authentic learning have an impact on the common problem-solving skills of students. Therefore, the purpose of this study is to analyze the effectiveness of a static fluid module with authentic learning to practice student problem-solving skills. This research is research and development using the 4-D model (Define, Design, Develop, Disseminate). Class trials using one group pre-test and post-test design. The subjects of the research trial were 33 students of class XB SMA in Banjarmasin. The data were obtained through tests of problem-solving skills. The results showed that the module was effective because the results of Mann Whitney test were sig. = 0.00; means there is a significant increase in problem-solving skills. Also, the students' problem-solving skills were in the very good category. Thus, a static fluid module with authentic learning is effective for practicing student problem-solving skills.